(untitled) (Research, Society and Development, 2022)
Respiratory diseases are commonly related to grain mills in association with fungi. Pigeons (Columba livia) are a potential source of pathogenic fungi and a public health concern, causing economic damages in urban areas. We aimed to determine the tracheal and pulmonary mycobiota of pigeons captured in a grain mill, identifying potentially pathogenic fungi. Captured pigeons were euthanized for the collection of tracheal secretion and lungs in saline suspensions for culture (100µL) in Sabouraud dextrose agar with chloramphenicol (48h/28°C). Yeasts were evaluated after Gram staining in microscopy and cultured in Hicrome®Candida agar, while lactophenol cotton blue solution was used in filamentous fungi/molds. Mycological identification keys were used for the genus determination. 207 fungal (9 genus) were isolated from the trachea and lungs of 21 pigeons captured: 199 molds (96.14%) and 8 yeast (3.86%). Aspergillus spp., Rhizopus spp., Penicillium spp. and Candida spp. were the most prevalent, mainly in lungs. We confirmed yeasts and molds from pigeons, increasing the potential risks for chronic or acute diseases after contact with several fungi from pigeons. A greater control of the presence of pigeons in the work environment is necessary.